Pathologic Skull Fracture in a Near-Term Neonate with Arthrochalasia Type Ehlers-Danlos Syndrome: A Case Report. (7th February 2022) - Liu, Yi Ariel; Chijiwa, Chieko; Dunham, Christopher P.; Jamieson, Douglas H.; Solimano, Alfonso; Schalkwyk, Julianne van; Patel, Millan S.; Lee, Anna F.
Abstract: Background: Arthrochalasia type Ehlers-Danlos Syndrome (EDS) is a connective tissue disease characterized by severe generalized joint hypermobility, congenital bilateral hip dislocations, and recurrent joint subluxations and dislocations. Only one study has reported bone fragility resulting in fractures. The genetic abnormality underlying this disorder is a variant in the COL1A1 gene causing entire or partial loss of exon 6, resulting in defective type 1 collagen synthesis. Case Report: We report a female infant born at 35 weeks of gestation presenting with pathologic skull fracture following vaginal delivery. Genetic testing revealed a pathogenic variant in the COL1A1 gene (c.472-1G > C), consistent with arthrochalasia type EDS, reported previously. Conclusion: This report adds pathologic fractures to the phenotypic breadth of this type of EDS and reinforces the importance of including the condition on the differential diagnosis when early onset non-accidental injury or trauma is being considered.